Analysis of the Features of Corporate Governance by the State: Similarity and Difference of Models - ZRYBNIEVA, Iryna; Martynyshyn, Y; Kukin, I; Khlystun, O; Pidlisnyi, Y (International Journal of Computer Science and Network Security, 2021)
The article formulates the key characteristics and features of country models of corporate governance. It was revealed that all countries are characterized by a fairly high concentration of ownership, insider control; Key gaps in the implementation of corporate governance principles were found: transparency and disclosure of information, protection of shareholders' rights, gender diversity of boards of directors, implementation of recommendations on the share of independent directors; The criterion of countries' efficiency (total investments) was identified and recommendations for their improvement were developed.